Article Commentary: Educating Future Environmental Health Professionals - Paul L. Knechtges; Timothy R. Kelley (SAGE Publishing, 2015)
Future environmental health problems will require a new generation of educated and trained professionals. Efforts to enhance the environmental public health workforce have been promoted by several organizations. While progress has been measured by these organizations, many environmental health academic programs are experiencing budget reductions and lower enrollments. One of the reasons for this trend is the so-called higher education crisis . We argue that training is not equivalent to education in the environmental health sciences, albeit the two terms are often used interchangeably. Organizations involved with the education, training, and credentialing of environmental health professionals must work together to ensure the viability and effectiveness of environmental health academic programs.